CRISPR/Cas9‐mediated knockout of the abdominal‐B homeotic gene in the global pest, fall armyworm (Spodoptera frugiperda) - Liu, Xiao‐Guang; Zhao, Te; Qiu, Qi‐Qi; Wang, Cong‐Ke; Li, Tian‐Liang; Liu, Xiao‐Long; Wang, Li; Wang, Qin‐Qin; Zhou, Lin (Insect molecular biology, 2025)
The Homeotic complex (Hox) genes play a crucial role in determining segment identity and appendage morphology in bilaterian animals along the antero‐posterior axis. Recent studies have expanded to agricultural pests such as fall armyworm (FAW), scientifically known as Spodoptera frugiperda J. E. Smith (Lepidoptera: Noctuidae), which significantly threatens global agricultural productivity. However, the specific role of the hox gene Sfabd‐B in FAW remains unexplored. This research investigates the spatial and temporal expression patterns of Sfabd‐B in various tissues at different developmental stages using quantitative real‐time polymerase chain reaction (qRT‐PCR). Additionally, we explored the potential function of the Sfabd‐B gene located in the FAW genome using CRISPR/Cas9 technology. The larval mutant phenotypes can be classified into three subgroups as compared with wild‐type individuals, that is, an excess of pedis in the posterior abdomen, deficient pedis due to segmental fusion and deviations in the posterior abdominal segments. Importantly, significant differences in mutant phenotypes between male and female individuals were also evident during the pupal and adult phases. Notably, both the decapentaplegic (dpp) and cuticular protein 12 (cp 12) genes displayed a substantial marked decrease in expression levels in the copulatory organ of male mutants and the ovipositor of female mutants compared with the wild type. These findings highlight the importance of Sfabd‐B in genital tract patterning, providing a potential target for improving genetic control. The CRISPR/Cas 9 system can modify the Abd‐B gene, leading to the development of various mutant phenotypes during the larval, pupal and adult stages of FAW. Some developmental genes such as decapentaplegic gene and cuticular protein12 were downregulated in the copulatory organ of mutant males and the ovipositor of mutant females compared with the wild type. Abd‐B plays an important role in determining segment identity and appendage morphology of S. frugiperda.